Monitoring and Evaluation Electrical Power Control in Solar Power Systems Based on IoT - Freddy Artadima Silaban; Evanendra Nur Wisnu Putra; Lukman Madriavin Silalahi (Universitas Raharja, 2024)
This study aims to develop a monitoring and electrical power control system for solar power systems based on IoT. The problem addressed is how to monitor and control the electrical power usage from solar panels in real-time over the internet, as well as how to limit the electrical power used by AC loads for energy efficiency. The system is equipped with sensors to measure current, voltage, and light intensity, controlled by an ESP32 microcontroller. Sensor data is processed and displayed in the form of graphs on a web page in real-time. The system also includes additional controls to connect and disconnect the electric current to AC loads, and limit the electrical power, allowing users to manage electrical energy usage efficiently. The research methodology includes several stages: designing the system block diagram, developing the hardware and software, implementing and integrating sensors with the ESP32 microcontroller, and testing the entire system. The results show that the prototype system can function according to the initial design. The system can record current, voltage, power, and light intensity in real-time and display them as graphs and tables on the website. AC load control and power limiting on AC loads can operate according to user commands. Measurements from a 10 Wp solar panel show maximum intensity around noon under sunny conditions, producing a current of up to 0.45 Ampere. The efficiency of the solar panel in this prototype is 12.16%, indicating a need for improvement for more effective use. The main contribution of this research is the development of an integrated monitoring system with web-based electrical power control, enabling users to monitor and manage solar power systems efficiently and in real-time